RESPON BEBERAPA GALUR TOMAT (Lycopersicum esculentum Mill.) TERHADAP PENYAKIT BUSUK DAUN (Phytophthora infestans (Mont.) de Bary) - Gungun Wiguna; Rahmat Sutarya; Yenny Muliani (MEDIAGRO, 2015)
Tomato varieties cultivated in Indonesia is still susceptible to late blight. This research aims to determine the level of resistance of some strains of tomato to late blight. The research was conducted at the field trial Indonesian Vegetable Research Institute Lembang located at an altitude of ± 1250 above sea level. The type of soil Andisol temperate type B, with a daily average temperature ranging between  19-24  °  C,  relative  humidity  ranged  between  34-90%  and  an  average rainfall  of  2207.5  mm/year.  The  research  was  conducted  from  March  to  May 2015.  The  studies  used  randomized  complete  block  design  (RCBD)  with  16 treatment  lines/varieties  consisting  of  15  strains  of  balitsa  tomato  germplasm collection and the commercial varieties called "Intrend" as a control. The results showed that there are seven strains that have the same relative level of resistance to  the  control  varieties  of  the  intensity  of  late  blight  caused  by  the  fungus Phytophthora infestans (Mont.) De Bary, the strains are 1602-14, 1608-14, 1611-14,  1616-14, 1618-14,  1620-14, and  1621-14. Furthermore,  these  strains can  be used in further studies to obtain varieties resistant to late blight.Keywords: Late blight, line, tomato, variety.